Effectiveness of civic competence training among adult students with mild intellectual disability - Klaudia Anna Wos; Celina Kamecka-Antczak; Mateusz Szafrański (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Social inclusion of people with intellectual disabilities is determined by the opportunity to acquire appropriate social and civic competences. These competences are an essential condition for active participation in social life by each individual. This article discusses the issue of civic competence developed during formal and informal training. The considerations are based on conclusions from the research of social and civic competences conducted in a special vocational school for students with mild intellectual disabilities. The aim  of the research was to check the effectiveness of civic competences training. The research population was made up of students taking part in the one-semester project "Young Citizen" and students from the control group not covered by the project.  In the exploration, the researchers used Questionnaires of Social and Professional Competences for people with  mental disabilities and their carers and also author's interview questionnaire on selected civic competences. The research results show that all respondents have a similar range of basic knowledge about society. Students taking part in the training have broader competences in the fild of civic issues.